Novel Combined Toxicity Indices (CTI) to assess the ecological risk of metals in sediments dependent on fractions and total metal content, application on Qarun Lake sediment, case study - Mohamed E. Goher; Alaa I. Khedr (Water Cycle)
Fractions and total contents of 21 heavy metals were evaluated in Qarun Lake sediment, a closed and shallow turbid saline lake. The metal contents in the sediments were in the following order: Fe > Al > Ti > Mn > Sr > Zn > Cr > Pb > Ba > Ni > B > Cu > Li > Co > As > Ga > Cd > Se > Bi > Ag > Hg. Several indices based on the total content (T-indices) or the fraction ratios (F-indices) assessed the pollution degree of the sediment. All the indices used revealed that the sediment of Qarun Lake suffers from different degrees of metal pollution. The T-indices evaluate the pollution or potential risk depending on the total content of metals, regardless of the species of these metals (hazardous mobile or non-mobile forms). Also, the F-indices evaluate pollution depending on the fraction ratios of metals, regardless of their metal content (even if at a deficient level). This study suggested a new combined toxicity index (CTI) and mean CTI (m-CTI) to combine T-indices and F-indices to assess the potential toxicity of metals and the pollution levels of sites, respectively. Based on integrated T-indices, all selected sites in Qarun Lake were extremely or highly polluted. Also, the GCF (as F-index) revealed that the investigated metals highly contaminated all sites. In contrast, according to the m-CTI, sites 1, 3, and 4 were highly polluted, while sites 2, 5, and 6 were moderately polluted. The present study's findings indicate that using CTI and m-CTI may be more favorable and accurate in assessing the metal pollution status of sediment than using T-indices or F-indices separately.